Sistem Monitoring Limbah Oli Menggunakan Arduino Uno Berbasis Lora - Adi Galih Utomo; Diana Alia; Anak Agung Istri Sri Wahyuni (Jurnal Penelitian Rumpun Ilmu Teknik, 2024)
Oil is one of the essential lubricating materials for machinery, especially on ships. With the abundant use of oil, waste oil is generated from the remaining oil discharge, causing dirty oil to become waste oil. To monitor the disposal of waste oil by ships, "Waste Oil Monitoring System Using LoRa-Based Arduino Uno" has been created. This tool is also equipped with sensors that can distinguish seawater and waste oil and uses the LoRa system. This method involves researching problems that exist in the shipping environment. The presence of waste oil pollution was successfully detected in the results of this study, and can be monitored remotely through an LCD display with LoRa. In this case study, the device made can detect waste oil and can distinguish it from sea water. The purpose of making this tool is to detect the presence of oil in sea waters in order to reduce and prevent waste oil pollution that can spread widely in sea waters. The system can function properly because there is an error of 2.18% in the fresh water test, 2.08% in the seawater test, 4.55% in the oil test, and 3.08% in the seawater and oil mixture test compared between the pH sensor and the pH meter. The system can work well using LoRa Ra-02, and the transmitted data can be reached stably at a distance of 205m, but if it exceeds that distance, the data can no longer be received by the receiver or becomes invalid.